2013
DOI: 10.1007/s11120-013-9943-x
|View full text |Cite
|
Sign up to set email alerts
|

Flux balance analysis of Chlorella sp. FC2 IITG under photoautotrophic and heterotrophic growth conditions

Abstract: Quantification of carbon flux distribution in the metabolic network of microalgae remains important to understand the complex interplay between energy metabolism, carbon fixation, and assimilation pathways. This is even more relevant with respect to cyclic metabolism of microalgae under light-dark cycle. In the present study, flux balance analysis (FBA) was carried out for an indigenous isolate Chlorella sp. FC2 IITG under photoautotrophic and heterotrophic growth conditions. A shift in intracellular flux dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…[39], C. reinhardtii [23], and Chlorella sp. [79]. Mixotrophic growth, as a kind of hybrid condition, has shown biomass yields falling between ones observed for autotrophic and heterotrophic.…”
Section: Lessons Learned From Metabolic Modeling Of Oleaginous Phototmentioning
confidence: 99%
See 1 more Smart Citation
“…[39], C. reinhardtii [23], and Chlorella sp. [79]. Mixotrophic growth, as a kind of hybrid condition, has shown biomass yields falling between ones observed for autotrophic and heterotrophic.…”
Section: Lessons Learned From Metabolic Modeling Of Oleaginous Phototmentioning
confidence: 99%
“…Overcoming the steady-state assumption of standard FBA is vital for the modeling of highly dynamic systems, which are characteristic of photosynthetic microorganisms [33, 37, 79]. These organisms have evolved under cyclic light/dark conditions, which require switching between different phenotypic states.…”
Section: Introductionmentioning
confidence: 99%
“…(Table II) assume that the fluxes differ between light and dark only by the layout of the core carbon network (tricarboxylic acid, glycolysis, and PPP), and the rest of the metabolism (synthesis of amino acids, DNA, and RNA) does not vary significantly in terms of relative fluxes (Yang et al, 2000;Muthuraj et al, 2013;Wu et al, 2015). Despite previous reports that assume the lack of change in the flux distribution for nucleotide metabolism (Yang et al, 2000;Muthuraj et al, 2013;Wu et al, 2015), we found that fluxes vary widely depending on the growth condition. Our results suggest that the anabolic part of the metabolism is not independent of growth conditions, and iCZ843 provides an accurate qualitative and quantitative analysis of the metabolism.…”
Section: Flux Distributionmentioning
confidence: 99%
“…The relation of nucleotide composition (28 RNA/DNA) was taken from Muthuraj et al (2013). Literature and experimental data were normalized assuming an idealized size and weight for C. vulgaris (see below).…”
Section: Biomass Composition and Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation